Transport and lasing in topological photonic systems - Chattopadhyay, Udvas (Nanyang Technological University, 2021)
This thesis concerns the study of novel topological transport phenomena in photonic systems, particularly in valley photonic crystals, Weyl semimetals and photonic Chern insulators; and lasing in a valley photonic crystal.